Role of Phytochemicals in Prevention of Oral Diseases - Sunira Chandra; Anjana S Bagewadi; Arvind Shetti (Wolters Kluwer Medknow Publications, 2007)
The art of medicine consist in amusing the patient, while nature cures the disease". Consuming a diet rich in plant food will provide a milieu of phytochemicals (non-nutritive plant chemicals that have protective or disease preventive properties). The additive and synergistic effects of phytochemicals in fruit and vegetables are responsible for their potent antioxidant and anticancer activities, and that the benefit of a diet rich in fruit and vegetables is attributed to the complex mixture of phytochemicals present in whole foods. The aim of this paper is to highlight and discuss the importance of natural chemical substances available in fruits, vegetables and herbs as they interfere with multiple important cellular pathways and this property is utilized for the prevention and treatment of oral diseases.